Medical management of deliberate drug overdose: A neglected area for suicide prevention?. Issue 1 (20th January 2004) - Gunnell, D; Ho, D; Murray, V
Abstract : Objectives: Overdoses account for a quarter of all suicides in England. The number of people who survive the immediate effects of their overdose long enough to reach medical attention, but who subsequently die in hospital is unknown. The aim of this study was to determine the proportion of overdose suicides dying in hospital and describe their sociodemographic characteristics. Method: Cross sectional analysis of routinely collected Hospital Episode Statistics data for England (1997 to 1999) to identify hospital admissions for overdose among people aged 12+ and the outcome of these admissions. Results: Between 1997 and 1999 there were 233 756 hospital admissions for overdose, 1149 (0.5%) of these ended in the death of the patient such deaths accounted for 29% of all overdose suicides and 7% of total suicides. The median time between admission and death was three days (interquartile range one to nine days). The most commonly identified drugs taken in fatal overdose were paracetamol compounds, benzodiazepines, and tricyclic/tetracyclic antidepressants. Conclusion: Around a quarter of all overdose suicide deaths occur subsequent to hospital admission. Further more detailed research is required to discover if better pre-admission and inhospital medical management of those taking serious overdoses may prevent some of these deaths.